1993
DOI: 10.1002/jrs.1250241207
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of (DMSO)2Fe(II)PPIX to form a transient five‐coordinate complex as studied using transient resonance Raman spectroscopy

Abstract: Resonance Raman spectra of iron(1I) protoporphyrin IX [ Fe(II)PP] in dimethyl sulfoxide (DMSO) and deuterated DMSO were obtained at high and low photon densities using 10 ns laser pulses. At low photon density, comparison of the Raman spectra of the complex with those of carbonmonoxy-hemoglobin indicates that a lowspin, six-coordinate (DMSO),Fe(lI)PP complex exists; at high photon density, spectral comparisons with deoxyhemoglobin and the 2-methylimidazole heme complex (2-Melm)Fe(II)PP indicate that a transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…The optical absorption of the (DMSO) 2 Fe II PPIX and (CO)(DMSO)Fe II PPIX complexes are displayed in Figure . The optical absorption spectrum of the (DMSO) 2 Fe II PPIX displays a Soret maximum at 424 nm with visible bands located at 556 nm (α-band) and 527 nm (β-band) consistent with previous results. , The positions of these bands are characteristic of six-coordinate, low-spin heme complexes (see Table ). Exposure of the (DMSO) 2 Fe II PPIX to CO results in a hypsochromic shift in the Soret band to 415 nm and bathochromic shifts in both the α- and β-bands to 568 and 535 nm, respectively (Figure , trace b).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The optical absorption of the (DMSO) 2 Fe II PPIX and (CO)(DMSO)Fe II PPIX complexes are displayed in Figure . The optical absorption spectrum of the (DMSO) 2 Fe II PPIX displays a Soret maximum at 424 nm with visible bands located at 556 nm (α-band) and 527 nm (β-band) consistent with previous results. , The positions of these bands are characteristic of six-coordinate, low-spin heme complexes (see Table ). Exposure of the (DMSO) 2 Fe II PPIX to CO results in a hypsochromic shift in the Soret band to 415 nm and bathochromic shifts in both the α- and β-bands to 568 and 535 nm, respectively (Figure , trace b).…”
Section: Resultssupporting
confidence: 89%
“…Transient Absorption Studies of (DMSO) 2 Fe II PPIX and (CO)(DMSO) Fe II PPIX Complexes. Previous resonance Raman and transient absorption studies have demonstrated that the (DMSO) 2 Fe II PPIX complex is photolabile. , The photolysis product displays an absorption difference spectrum with an absorption maximum at 435 nm and a minimum at 423 nm. These studies have further shown that the decay of the (DMSO)Fe II PPIX transient occurs monophasically by rebinding a DMSO ligand to the vacant sixth-coordination site.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Band-gap excitation of the thin films immersed in Ar-purged solvent resulted in the reduction of Fe III to Fe II and a bathochromic shift in the Soret band for all ligations (Figure and Table ) . In the ferrous state, the axial ligands were identified clearly as DMSO or py by examination of the Q-band region of the visible absorption spectrum. , The axial ligands for thin films immersed in methanol are unknown but for consistency are referred to as (MeOH) 2 Fe III/II PPIX/TiO 2 .…”
Section: Resultsmentioning
confidence: 99%